ANALISIS YURIDIS TINDAK KEKERASAN SEKSUAL TERHADAP PEREMPUAN - Chairan, A. Tenripadang (DIKTUM: Jurnal Syariah dan Hukum, 2010)
This article unearths the sexual abuse to women. Using legal approach, this study reveals that the goal of law in criminal punishment is essentially to protect the victim from crime, especially raping. The criminal punishment to the person who commits crime is the right of the victim who has suffered from psychological and physical aspects. Although the goal of the law is very ideal, the implementation of the law is still far from ideal, since the rights of the victims of raping are often abandoned. This is evident if we refer to the regulations in the Criminal Punishment Law that normatively neglects the protection of the victim’s basic rights. In addition, the goal of the law in its juridical (normative) substance has not been in harmony with the substance of Islamic law.